Unmet Psychosocial Needs of Patients Newly Diagnosed with Ulcerative Colitis: Results from the Nationwide Prospective Cohort Study in Korea - Jung Rock Moon; Chang Kyun Lee; Sung Noh Hong; Jong Pil Im; Byong Duk Ye; Jae Myung Cha; Sung-Ae Jung; Kang-Moon Lee; Dong Il Park; Yoon Tae Jeen; Young Sook Park; Jae Hee Cheon; et al. (Gut and liver, 2020)
Background/Aims: Limited data are available regarding psychosocial distress at the time of diagnosis of ulcerative colitis (UC). We investigated the psychosocial burden and factors related to poor health-related quality of life (HRQL) among patients newly diagnosed with moderate-to-severe UC who were affiliated with the nationwide prospective cohort study. Methods: Within the first 4 weeks of UC diagnosis, all patients were assessed using the Hospital Anxiety and Depression Scale (HADS), Work Productivity and Activity Impairment questionnaire, Inflammatory Bowel Disease Questionnaire (IBDQ), and 12-Item Short Form (SF-12) health survey. A multiple linear regression model was used to identify factors associated with HRQL. Results: Between August 2014 and February 2017, 355 patients completed questionnaires. Significant mood disorders requiring psychological interventions, defined by a HADS score ≥11, were identified in 16.7% (anxiety) and 20.6% (depression) of patients. Patients with severe disease were more likely to have presenteeism, loss of work productivity, and activity loss than those with moderate disease (all p<0.05). Significant mood disorders had the strongest negative relationship with total IBDQ score, which indicates disease-specific HRQL (β coefficient: –22.1 for depression and –40.0 for anxiety, p<0.001). The scores of all SF-12 dimensions, which indicate general HRQL, were remarkably decreased in the study population compared indirectly with previously reported scores in the general population. The Mayo score, C-reactive protein level, and white blood cell count showed significant negative associations with the IBDQ score (p<0.05). Conclusions: Psychosocial screening and timely interventions should be incorporated into the initial care of patients newly diagnosed with UC. KCI Citation Count: 0